Pemeriksaan Kadar Gula Darah Sewaktu pada Remaja di SMAN 7 Denpasar - Laksmita, Saka; Apriyanthi, Desak Putu Risky Vidika; Widayanti, Ni Putu; Aryasa, Wayan Tanjung; Artini, Ni Putu Rahayu; Iriani, Yulidia (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
People in urban areas tend to have unhealthy lifestyles, especially teenagers. This can trigger various diseases. Health status needs to be considered from an early age, especially paying attention to the intake of sugar in the body. Excess sugar levels in the blood are one of the causes of diabetes mellitus. Measurement of blood sugar (GDS) in adolescents of SMAN 7 Denpasar aims to screen for Diabetes Mellitus (DM) to detect this disease early. The method is done by checking the blood sugar test (GDS), weight, and height. The results of the blood sugar test in this community service activity showed that out of 50 students with a ratio of male and female percentages of 40% and 60% respectively, only 4% were identified with low blood sugar levels while the remaining 96% had normal blood sugar levels. The conclusion of the community service at SMAN 7 Denpasar is that most of the students have normal blood sugar levels.